Inventory management of 50 kg packaged cement products with a lot sizing ratio (case study: XYZ warehouse) - Annisa Sherina Rahmadhani Hasibuan; Wahyuda Wahyuda; Farida Djumiati Sitania (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
XYZ is a trading and shipping company for building needs. The problem experienced by XYZ Warehouse is the high demand for Conch 50 kg cement products without being balanced with good inventory management so that companies often experience shortages and excess supplies which can increase inventory costs. Therefore, good inventory planning and control are needed to make the costs incurred is more optimal. The model used in this study is the Economic Order Quantity (EOQ) model by calculating safety stock and reorder points to avoid demand uncertainty. Before calculating the inventory model, forecasting was done using the Moving Average 6 method as the chosen method with MAD 4,712,852, MSE 37,283,346,809, and MAPE 15.502%. Based on the calculation results, the optimal order quantity was 1,868, safety stock was 185, and reorder point was 1,320. Other than that, the lot-sizing technique was also carried out using the EOQ, LFL, POQ, and Silver Meal methods. Based on the calculation result, the lot-sizing technique that provides a minimum total cost was the LFL method with a total cost of Rp. 1,430,406.61 and savings up to 77.04%, followed by the EOQ method with a total cost of Rp. 1,918,668.55 and savings up to 69.21%. Also, the POQ and Silver Meal method with a total cost of Rp. 2,106,571.61 and savings up to 66.19%. PT. XYZ merupakan perusahaan yang beroperasi dalam sektor perdagangan barang dan jasa pengiriman untuk keperluan bahan bangunan. Permasalahan yang dihadapi Gudang XYZ adalah tingginya permintaan produk Semen Conch 50 kg tanpa diimbangi pengelolaan persediaan yang baik sehingga kerap mengalami kekurangan maupun kelebihan persediaan di mana hal tersebut dapat meningkatkan biaya persediaan. Oleh karena itu, dibutuhkan suatu perencanaan dan pengelolaan persediaan yang baik sehingga biaya yang dikeluarkan pun lebih optimal. Model yang dimanfaatkan dalam penelitian ini adalah model economic order quantity (EOQ) dengan memperhitungkan safety stock dan reorder point untuk menghindari ketidakpastian permintaan. Sebelum dilakukan perhitungan model persediaan, terlebih dahulu dilakukan peramalan dengan metode moving average 6 sebagai metode terpilih dengan MAD 4.712,852, MSE 37.283.346,809, MAPE 15,502%. Berdasarkan hasil perhitungan model EOQ, diperoleh Q optimal sebanyak 1.868 sak, safety stock 185 sak, dan reorder point 1.320 sak. Selain itu, dilakukan pula lot sizing dengan metode EOQ, LFL, POQ, dan Silver Meal. Berdasarkan hasil perhitungan, lot sizing yang memberikan total biaya minimum adalah LFL dengan total biaya sebesar Rp. 1.430.406,61 dan penghematan mencapai 77,04%, kemudian diikuti oleh EOQ dengan total biaya sebesar Rp. 1.918.668,55 dan penghematan mencapai 69,21%, dan POQ serta Silver Meal dengan total biaya sebesar Rp. 2.106.571,61 dan penghematan mencapai 66,19%.